March Market Madness: The Impact of Value‐Irrelevant Events on the Market Pricing of Earnings News1. (16th July 2015) - Drake, Michael S.; Gee, Kurt H.; Thornock, Jacob R.
Abstract: Each year, the NCAA basketball tournament (March Madness) is a daytime distraction for millions of people, providing a largely exogenous shock to investor attention. We investigate whether March Madness influences the market response to earnings by diverting investor attention away from earnings news. We find that the price reaction to earnings news released during March Madness is muted. This result generally holds across several samples and additional analyses. We also find that the result is more muted for low institutional ownership firms, consistent with the effect being driven by less‐sophisticated investors. Furthermore, we find that it takes the market 30 to 60 days to correct for the distraction effect. Overall, we provide a unique test of the theory of limited attention by documenting that extraneous events can have a significant impact on the pricing of earnings.